History Is What Bites: Zombies, Race, and the Limits of Biopower in Colson Whitehead's Zone One. Issue 3 (2015) - Hurley, Jessica
Abstract : This paper argues that the zombie serves as the limit point of biopower because it introduces an ungovernable third term into the biopolitical poles of human and non-human, life and death: the ex-human, the undead. Taking race as its central biopolitical concern, the first part of the paper reads the visual tensions between whiteness and blackness in Hollywood representations of the zombie. I then turn to Colson Whitehead's 2010 novel Zone One, arguing that in this novel the zombie figures the return of a repressed history of racial trauma in a contemporary moment in which biopower operates increasingly under the sign of the "postracial."